Natural History of 321 Flatfoot Reconstructions in Adult Acquired Flatfoot Deformity Over a 14-Year Period. Issue 3 (June 2021) - Goss, Madison; Stauch, Christopher; Lewcun, Joseph; Ridenour, Ryan; King, Jesse; Juliano, Paul; Aynardi, Michael
The purpose of this study was to report the natural history, demographics, and mechanisms of requirement for additional surgery in patients undergoing flatfoot reconstruction for adult acquired flatfoot. A total of 321 consecutive patients undergoing flatfoot reconstruction over a 14-year period were included (2002-2016). All procedures were performed by a senior orthopaedic foot and ankle surgeon at our institution. Demographic data, operative reports, clinic notes, and radiographs were available for review. Statistical analysis included calculation of relative risk (RR) ratios. The majority of patients were female (83.2%, ) and most patients were overweight with a body mass index greater than 25 kg/m 2 (56.4%). Patient comorbidities included diabetes (13.7%) and rheumatoid arthritis (3.7%). Additional surgery was required for 54 patients (16.8%). The most common reasons for additional surgery were the following: painful calcaneal hardware (57.4%), conversion to triple arthrodesis (16.7%), and wound healing complications (9.1%). An increased risk of need for additional surgery was associated with female gender (RR = 3.4; P = .0005), smoking status (RR = 1.9; P = .0081), and age (<60 years of age; RR = 1.8; P = .042). Although retrospective, the results provide insight into the natural history of this procedure. Clinicians may use these data to appropriately counsel patients who are at increased risk of requirement for additional surgery, such as smokers, women, and patients <60 years old, regarding treatment options. Levels of Evidence: Level IV